PANDANGAN MASYARAKAT MUDA DAN DEWASA PADA PENGGUNAAN KATA-KATA KASAR DALAM PERCAKAPAN - Darmawan, Adhitya; Yulianti, Wiwik; Yustanto, Henry (Universitas Sebelas Maret, 2024)
This research analyses how young and old people have different views on swearing in conversation. There are several factors including, social, developmental, cultural, and individual factors that shape difference amongst the people. The views on the values are based on philosophical theory. The focus is not only on how people give their point of view on swearing in conversation but also what they think about their suggestion of the use of swearing. This is a qualitative research with sociolinguistic approach and uses observation where there are ten people who are asked to give opinions on swearing. The findings show that there are youngsters who view swearing as a regular phenomenon while the mature ones are rather the opposite. The discussion covers how the different age puts a gap on the understanding and usage of swearing. In conclusion, the opinions from ten people are seemingly contrast but what is similar is the suggestion from the interviewed people which is to adjust the use of swearing carefully.